1
$\begingroup$

The problem says:

What is $f'(0)$, given that

$f\left(\sin x −\frac{\sqrt 3}{2}\right) = f(3x − \pi) + 3x − \pi$, $x \in [−\pi/2, \pi/2]$.

So I called $g(x) = \sin x −\dfrac{\sqrt 3}{2}$ and $h(x)=3x − \pi$.

Since $f(g(x)-h(x))=3x − \pi$, I called $g(x)-h(x) = j(x) = \sin x −\frac{\sqrt 3}{2} - 3x +\pi$

I imagined that I should find the function $f$, by finding the inverse of $j(x)$ and doing $(f \circ j \circ j^{-1})(x)$ but I discovered that it is too much difficult.

I guess that's not the best way.

What should I do?

$\endgroup$
  • $\begingroup$ But $f(g(x) - h(x))$ is not $3x - \pi$. You can only say that $f(g(x)) - f(h(x)) = 3x - \pi$. $f(a) - f(b) \ne f(a - b)$ (in general). $\endgroup$ – M. Vinay Apr 26 '16 at 5:22
  • $\begingroup$ OMG, that's true. So I really don't know where to go $\endgroup$ – Carlos Mendes Apr 26 '16 at 5:32
  • $\begingroup$ Just differentiate, use chain rule, and then try to get $f'(0)$ using an appropriate value of $x$. $\endgroup$ – M. Vinay Apr 26 '16 at 5:47
1
$\begingroup$

Given: $$f(\sin x - \frac{\sqrt 3}{2}) = f(3x-\pi) + 3x - \pi$$ Taking derivatives on both sides w.r.t. $x$, we get, $$f'(\sin x - \frac{\sqrt 3}{2}).\cos x = 3.f'(3x-\pi) + 3$$ Put $x=\frac{\pi}{3}$, we get, $$f'(\sin \frac{\pi}{3} - \frac{\sqrt 3}{2}).\cos \frac{\pi}{3} = 3.f'(3.\frac{\pi}{3}-\pi) + 3$$ $$f'(0).\frac{1}{2} = 3.f'(0) + 3$$ Solving for $f'(0)$, we get, $$f'(0)=-\frac{6}{5}$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.